Digital Health for Precision Prevention - Mougin, Fleur; Hollis, Kate Fultz; Soualmia, Lina F. (Yearbook of Medical Informatics, 2024)
Objectives: To introduce the 2024 International Medical Informatics Association (IMIA) Year-book by the editors.Methods: The editorial provides an introduction and overview to the 2024 IMIA Yearbook with the special theme, “Digital Health for Precision in Prevention”. The special topic, the survey papers and some of the best papers selected this year by section editors are introduced. Changes in the Yearbook editorial board are also described.Results: IMIA Yearbook 2024 provides many perspectives on the popular topic called “Digital Health for Precision in Prevention”. The theme expresses the aim to provide the right intervention at the right time, adapted to the needs of each individual. Many sections presented original work on this year's theme, and all sections described notable contributions from 2023 in the various medical informatics specialties covered by the Yearbook.Conclusions: The theme of “Digital Health for Precision in Prevention” is very important now when the rapid and extensive variety of digital tools grow exponentially.
Keywords: Medical Informatics; Health Information Technology; Digital Health; Precision Prevention; IMIA Yearbook of Medical Informatics